PENINGKATAN KESEHATAN FISIK DAN MENTAL IBU HAMIL MELALUI PRENATAL YOGA - Dewi Susilawati; Novria Hesti; Nur Fadjri Nilakesuma (LPPM Universitas Abdurrab, 2022)
The results of interviews with the Chair of the Pregnant Women's Group at PMB Midwife Silvia Nova Sari, it was found that the number of pregnant women was 26 pregnant women, pregnant women who visited often complained of body pain, felt weak, short of breath, and sometimes also felt anxious about their pregnancy. The solutions given by midwives regarding the problems of pregnant women are only limited to ordinary education why these things can be experienced by pregnant women, midwives have not provided an education that is very effective in overcoming these problems, one of which is education with prenatal yoga techniques. The midwife also said that the class for pregnant women had never done prenatal yoga because there were no midwives who attended prenatal yoga training. This activity was carried out on September 23-24, 2021 at PMB Silvia Nova Sari, the Working Area of ​​the Air Cold Health Center with a target number of 8 pregnant women. This activity begins with providing education and then ends with the practice of yoga for pregnant women. The result of this service is an increase in the physical and mental health of pregnant women after prenatal yoga is carried out. The results of interviews with pregnant women where they said that after participating in this activity, they felt happy, even the aches they used to feel we're not so pronounced. It is hoped that with this activity pregnant women can apply it at home so that maternal health is maintained.